INTERMEDIATE ACCOUNTING INSTRUCTION –CIRCA, 1955. - Kerrigan, Harry D. (The Accounting Review, 1956)
Abstract The article presents intermediate accounting instructions in the year 1955. Instruction in intermediate accounting was surveyed through a questionnaire that was sent to 100 colleges in the spring of 1955. Answers were received from two-thirds of the colleges. The survey dealt with the state of instruction as it is, rather than as it might be, but the latter aspect was not entirely overlooked. The course seems to be firmly established in schools offering a more or less complete study of accounting. Schools with a three-year program in accounting offer the intermediate course in the second year, typically for the full year. The force of this impression is reduced, though not materially, by two further disclosures. Second, certain topics in a book were omitted, even in a year course. Leading the list of topics omitted is review of accounting process, which was mentioned 4 times. In the survey, it was asked that should the teachers be tagged for intermediate accounting as one of the specialized fields in which to teach. The answers received show that 31 schools regard the intermediate course as a specialized field, 16 do not, rotating teachers; have combination policies, and 12 pursue no positive policy on the question.